1972
DOI: 10.1136/hrt.34.5.520
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of atrial fibrillation in man.

Abstract: Quantitative studies on the sinoatrial (SA) node and internodal tracts in IOO heartsfrom patients coming to necropsy with atrialfibrillation have been carried out. In patients with atrialfibrillation developing only in the last two weeks of life, pulmonary emboli and acute pericarditis were common precipitating factors. Atrial dilatation was common but the SA node and internodal tracts were within normal limits. In contrast patients with long-term atrial fibrillation showed combinations of nodal artery stenosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
126
1
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(132 citation statements)
references
References 10 publications
4
126
1
1
Order By: Relevance
“…In addition to this 'tachycardiomyopathy' occurring at ventricular level, long-standing atrial fibrillation leads to a sort of atrial cardiomyopathy. This includes ultrastructural changes [24], an increase in atrial size [25], and a decrease in atrial contractility [26] that represent the anatomical and mechanical counterparts of the remodelling process, as well as a progressive depletion of atrial natriuretic peptide leading to an 'endocrinological silence' [27] It would appear logical to apply these general concepts suggesting a potentially detrimental role of atrial fibrillation to patients with heart failure, who have already a limited cardiac reserve and a reduced exercise tolerance. In contrast with these considerations, the impact of atrial fibrillation on mortality in patients with heart failure is controversial and, actually, most recent studies suggest that atrial fibrillation carries no independent risk.…”
Section: Clinical Rolementioning
confidence: 99%
“…In addition to this 'tachycardiomyopathy' occurring at ventricular level, long-standing atrial fibrillation leads to a sort of atrial cardiomyopathy. This includes ultrastructural changes [24], an increase in atrial size [25], and a decrease in atrial contractility [26] that represent the anatomical and mechanical counterparts of the remodelling process, as well as a progressive depletion of atrial natriuretic peptide leading to an 'endocrinological silence' [27] It would appear logical to apply these general concepts suggesting a potentially detrimental role of atrial fibrillation to patients with heart failure, who have already a limited cardiac reserve and a reduced exercise tolerance. In contrast with these considerations, the impact of atrial fibrillation on mortality in patients with heart failure is controversial and, actually, most recent studies suggest that atrial fibrillation carries no independent risk.…”
Section: Clinical Rolementioning
confidence: 99%
“…2 Increased amounts of atrial fibrosis were found in patients with AF, who also showed an activated angiotensin system. 3,4 In addition to angiotensin II-related changes, the amount of atrial fibrosis increases with patient age. 4 Another structural change commonly observed with increasing age in the heart is amyloidosis, which, like atrial fibrosis, may disturb atrial conduction.…”
mentioning
confidence: 99%
“…3,4 In addition to angiotensin II-related changes, the amount of atrial fibrosis increases with patient age. 4 Another structural change commonly observed with increasing age in the heart is amyloidosis, which, like atrial fibrosis, may disturb atrial conduction. Amyloidosis represents a diverse group of diseases characterized by the presence of extracellular proteinaceous deposits showing characteristic structural and tinctorial properties.…”
mentioning
confidence: 99%
“…2 patients AF was associated with loss of muscle fibers in the sinoatrial node and its approaches without any clear pathological cause. 1 Erickson and Lev have shown degenerative changes in the conduction system with age. 10 With this histologic background in mind, changes in the electrophysiologic properties of the atrial muscle with advancing age can be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Davies and Pomerance reported that AF in some aged patients was associated with loss of muscle fibers in the sinoatrial node and its approaches without any clear pathological cause. 1 Muscle loss with advancing age was found to be accompanied by an increase in fibrous tissue in both the sinoatrial node and the internodal tracts. [2][3][4] It was strongly suggested that muscle loss and increase of fibrosis in the atria is a slow but continuous process starting at about 60 years of age.…”
Section: Introductionmentioning
confidence: 99%